Chapter Eighteen: Sharing Power: Māori and Protect Areas - Mead, Aroha Te Pareake (Future challenges for Māori: he kōrero anamata, 2013)
"This collection of essays by 22 contributors, experts in their fields, represents the accumulated knowledge of a group of Māori scholars on a variety of contemporary issues, including Māori identity and self-determination, the environment, te reo Māori, education, social and economic issues, and governance and leadership. The collection is a result of a series of seminars organised by the MANU AO Academy, which is a national inter-university Māori Academy for academic and professional advancement"--Publisher information.
Keywords: government; mana motuhake; rangatiratanga; social conditions; sovereignty

Chapter 11: Maori Concepts and Practices of Rangatiratanga: "Sovereignty?" - Tomas, Nin (Sovereignty: Frontiers of Possibility, 2013)
Keywords: rangatiratanga; sovereignty; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi

A Small Issue of Sovereignty - Bargh, Maria (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: history; neoliberalism; political Ideologies; protest; sovereignty; tino rangatiratanga; trans-pacific partnership

Chapter 7: Papaki Rua Ngā Tai: Tides of Confluence: Māori and the State - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."--Book jacket.
Keywords: UNDRIP; crown policy; government relations; land tenure; law; mana motuhake; sovereignty; tino rangatiratanga; welfare policies

Chapter 8: Te Ngau o te Tai: The Sting of the Tide: Māori and the Law - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."--Book jacket.
Keywords: government relations; law; mana motuhake; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

Chapter 9: Rongotai: the Roar of the Ride: Māori in Parliament - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."--Book jacket.
Keywords: government relations; kāwanatanga; law; mana motuhake; māori electorates; māori seats; parliament; self-determination; sovereignty; tino rangatiratanga

The Treaty and the word: the colonization of Māori philosophy - Jackson, Moana (Justice, ethics and New Zealand society, 1992)
Keywords: environment; kaupapa māori; philosophy; print only; rangatiratanga; social justice; sovereignty; tiriti o waitangi/treaty of waitangi

Maori self-determination and a liberal theory of indigeneity - O'Sullivan, Dominic (Restoring Indigenous Self-Determination: Theoretical and Practical Approaches, 2014)
Indigenous peoples find themselves locked in power struggles with states and transnational actors who resist their claims, raising important questions in theory and practice. Edited by Marc Woons.
Keywords: rangatiratanga; self-determination; sovereignty

Chapter Six: Māori and Freshwater Law - Ruru, Jacinta (Future challenges for Māori: he kōrero anamata, 2013)
"This collection of essays by 22 contributors, experts in their fields, represents the accumulated knowledge of a group of Māori scholars on a variety of contemporary issues, including Māori identity and self-determination, the environment, te reo Māori, education, social and economic issues, and governance and leadership. The collection is a result of a series of seminars organised by the MANU AO Academy, which is a national inter-university Māori Academy for academic and professional advancement"--Publisher information.
Keywords: government; mana motuhake; rangatiratanga; social conditions; sovereignty